Low-complexity non-iterative hybrid precoding scheme for millimeter wave massive MIMO systems - Sharma, Neeraj; Gupta, Bhasker (International journal of electronics, 2022)
Conventional multiple-input multiple-output (MIMO) systems operating at sub-6 GHz frequencies generally employ fully digital precoding which requires dedicated radio frequency (RF) chain for each antenna element. However, this architecture is infeasible for the millimetre wave (mmWave) massive MIMO systems due to excessive power consumption and space constraints posed by large number of RF chains. Hence, hybrid precoding architecture, which utilises small size digital precoder followed by large size analog precoder, is employed for such systems. Due to the constant-magnitude hardware constraint on the phase shifter elements of analog precoder, efficient design of hybrid precoders is a challenge. In this paper, a low-complexity non-iterative hybrid precoder/combiner design is proposed for a single-user mmWave massive MIMO system. The analog RF precoder vectors are selected non-iteratively from the set of transmit array response vectors such that they are 'aligned' with the optimal precoder of the channel. Then, for the fixed analog precoder, the digital baseband precoder is evaluated using least square solution. Matrix operations like singular value decomposition, correlation and inversion are required only once. A similar approach is adopted for the design of hybrid combiners of the receiver. Simulation results show effectiveness of the proposed method in terms of spectral efficiency maximisation.